SMALL AREA ESTIMATION OF THE PERCENTAGE HOUSEHOLDS WITH FOOD EXPENDITURE SHARE MORE THAN 65 PERCENT IN LOW EXPENDITURE GROUP - Anjarwati, Niken Alfina; Ubaidillah, Azka (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
The right to get adequate food is a human right that must be fulfilled. Food insecurity is a problem that arises from not fulfilling food needs physically or economically. Food insecurity and poverty are interrelated. The United Nations prioritizes the elimination of poverty as the first goal and achieving food security as the second goal in the Sustainable Development Goals. In 2022, East Java had the highest percentage of households with a food expenditure share more than 65 percent in Java. The availability of data by expenditure group illustrates the economic status of households will assist the government in making targeted policies. However, the calculation of direct estimates at the regency level has not shown good precision, characterized by estimates with an RSE >25 percent. Therefore, this study aims to implement SAE HB Beta to improve the precision of the direct estimator. The result shows that SAE HB Beta produces a more precise estimation.